Comparison of valsartan and amlodipine on ambulatory blood pressure variability in hypertensive patients. (16th November 2016) - Eguchi, Kazuo; Imaizumi, Yuki; Kaihara, Toshiki; Hoshide, Satoshi; Kario, Kazuomi
ABSTRACT: We tested the hypothesis that calcium channel blockers (CCBs: amlodipine group, n = 38)) are superior to angiotensin receptor blockers (ARBs: valsartan group, n = 38) against ambulatory blood pressure variability (BPV) in untreated Japanese hypertensive patients. Both drugs significantly reduced ambulatory systolic and diastolic BP values. With regard to BPV, standard deviation (SD) in SBP did not change with the administration of either drug, but the ARB significantly increased SD in awake DBP (12 ± 4–14 ± 4 mmHg). The ARB also significantly increased the coefficients of variation (CVs)in awake and 24-h SBP/DBP (all P < 0.05), but amlodipine did not change the CV. CCB significantly reduced the maximum values of awake SBP (193 ± 24–182 ± 27 mmHg, P = 0.02), sleep SBP (156 ± 18–139 ± 14 mmHg, P < 0 .001), and awake and sleep DBP (P < 0.01 in both cases), but the ARB did not change the maximum BP values. In conclusion, a once-daily morning dose of CCB amlodipine was more effective at controlling ambulatory BPV than ARB valsartan, especially in reducing maximum BP levels.